Influence of cigarette smoke inhalation on an autogenous onlay bone graft area in rats with estrogen deficiency: A histomorphometric and immunohistochemistry study - Nunes, Camilla Magnoni Moretto [UNESP]; Bernardo, Daniella Vicensotto [UNESP]; Ferreira, Camila Lopes [UNESP]; Gomes, Mônica Fernandes [UNESP]; De Marco, Andrea Carvalho [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (MDPI, 2019)
Purpose: The present study aimed to evaluate the influence of cigarette smoke inhalation on an autogenous onlay bone graft area, either covered with a collagen membrane or not, in healthy and estrogen-deficient rats through histomorphometry and immunohistochemistry. Materials and Methods: Sixty female rats (Wistar), weighing 250-300 g, were randomly divided and allocated into groups (either exposed to cigarette smoke inhalation or not, ovariectomized and SHAM). After 15 days, the test group underwent cigarette smoke inhalation. Sixty days after exposition, autogenous bone grafting was only performed on all right hemimandibles, and the left ones underwent autogenous onlay bone grafting with the collagen membrane (BioGide®). The graft was harvested from the parietal bone and attached to the animals’ jaws (right and left). They were euthanized at 21, 45, and 60 days after grafting. Histological measurements and immunohistochemical analyses were performed, and results were submitted to a statistical analysis. Results: The addition of a collagen membrane to the bone graft proved more effcient in preserving graft area if compared to the graft area without a collagen membrane and the one associated with cigarette smoke inhalation at 21 (p = 0.0381) and 60 days (p = 0.0192), respectively. Cigarette smoke inhalation combined with ovariectomy promoted a significant reduction of the autogenous graft area at 21 and 60 days. At 45 days, no statistically significant results were observed. In the immunohistochemical analysis, the ovariectomized and smoking subgroups, combined or not with collagen membrane, received moderate and intense immunolabeling at 21 days for Receptor Activator of Nuclear Factor Kappa-B Ligand (RANKL) (p = 0.0017 and p = 0.0381, respectively). For Osteoprotegerin (OPG), intense immunolabeling was observed in most subgroups under analysis at 60 days. Conclusion: Smoking inhalation promoted resorption on the autogenous onlay bone graft, mainly when associated with ovariectomy. Furthermore, when associated with the collagen membrane, a lower resorption rate was observed if compared to the absence of the membrane.
Keywords: Bone regeneration; Estrogen deficiency; Smoking